2015
DOI: 10.1109/twc.2015.2443777
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Precoding and Capacity Analysis for Multiple-Antenna Wireless Systems With User Radiation Exposure Constraints

Abstract: Mobile handsets, classified as portable devices, are regulated on the amount of user electromagnetic exposure. The widely accepted exposure measurement is the specific absorption rate (SAR). Despite the prevalence of SAR constraints throughout the world, there has been barely any work on the design and analysis of communication signals for SAR-constrained wireless systems. In this paper, we show that multiple antenna systems greatly reduce the SAR measurements when proper precoders are used. 5G and beyond cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…However, in this latter paper the impact of hardware impairments are not taken into account. Additionally, the impact of regulatory electromagnetic exposure constraints has also been taken into account when designing multiple transmit antenna signals in [37]- [39]. Recently, the interplay between waveforms, amplifier efficiency, distortion and performance in the massive MIMO downlink was studied in [40].…”
Section: A Related Work and Contributions Of The Present Paper 1) Pap...mentioning
confidence: 99%
“…However, in this latter paper the impact of hardware impairments are not taken into account. Additionally, the impact of regulatory electromagnetic exposure constraints has also been taken into account when designing multiple transmit antenna signals in [37]- [39]. Recently, the interplay between waveforms, amplifier efficiency, distortion and performance in the massive MIMO downlink was studied in [40].…”
Section: A Related Work and Contributions Of The Present Paper 1) Pap...mentioning
confidence: 99%
“…As discussed, wireless communication devices are subject to SAR limitations. Previous reported results such as [15] and [16] have shown that the pointwise SAR value with multiple transmit antennas can be modeled as a quadratic form of the transmitted signal, and the SAR matrices fully describes the SAR measurement's dependence on the transmitted signals and are positive-definite conjugate-symmetric matrices.…”
Section: A System Modelmentioning
confidence: 99%
“…In [20], two system models were developed where one used transmit (Tx) channel state information (CSI) to perform beamforming at the receiver and the other, which did not have Tx CSI, but was able to be 'SAR aware', i.e., could exploit knowledge of SAR in order to boost Tx power but stay in SAR limits. A beamforming approach based on Tx CSI approach was then further developed in [21] where a dual information theoretical optimal and SAR reduction precoder was proposed. Using a rigorous mathematical analysis, it was shown that the waterfilling of singular value decomposition (SVD) based eigenmodes could be altered to make the dual accommodation of maximized data throughput and SAR reduction by implementing a precoder based on the SVD itself in conjunction with other precoder structures similar to the ones used in MIMO systems operating in spatially correlated channels.…”
Section: Introductionmentioning
confidence: 99%